Application Research of New Cementitious Composite Materials in Saline Soil Subgrade Aseismic Strengthening - Shuai Huang; Yuejun Lyu; Yanju Peng (Advances in Civil Engineering)
Saline soil affected by earthquakes and groundwater can lead to subgrade subsidence and collapse in highway construction. Consequently, considering the potential activity of the waste slag and magnesia, new cementitious composite materials used in solid saline soil were developed in our study. The unconfined compressive strengths of the saline soil solidified by the new cementitious composite materials with a combination of magnesium oxide, calcium oxide, gypsum, and mineral powder and cement were investigated, and the optimum dosage proportion of the new cementitious composite material for solidifying saline soil was determined; then the SEM, EDS, and XRD of the saline soil solidified by the new cementitious composite materials and cement were analysed. The research result showed that the saline soil solidified by our newly developed cementitious composite material showed compact internal structure and uniformly distributed soil particles; moreover, the new cementitious composite material exhibited a favourable solidifying effect on harmful ions in saline soil, and the Cl− trapping capacity of the new cementitious composite materials was stronger than that of cement. Finally, our developed cementitious composite material was applied to saline soil subgrade strengthening, and the displacement, acceleration, excess pore water pressure, and damage degree of the subgrade strengthening by our newly developed cementitious composite materials decreased remarkably; therefore, our newly developed cementitious composite material can improve the seismic behaviour of the saline soil subgrade and show potential future engineering application value.